2021
DOI: 10.3390/biom11091315
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Copper Disorders Influence the Olfactory Function in Adult Rats: Roles of Altered Adult Neurogenesis and Neurochemical Imbalance

Abstract: Disrupted systemic copper (Cu) homeostasis underlies neurodegenerative diseases with early symptoms including olfactory dysfunction. This study investigated the impact of Cu dyshomeostasis on olfactory function, adult neurogenesis, and neurochemical balance. Models of Cu deficiency (CuD) and Cu overload (CuO) were established by feeding adult rats with Cu-restricted diets plus ip. injection of a Cu chelator (ammonium tetrathiomolybdate) and excess Cu, respectively. CuD reduced Cu levels in the olfactory bulb (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 105 publications
(142 reference statements)
2
6
0
Order By: Relevance
“…The choroid plexus plays a critical role in regulating Cu homeostasis in the CSF [ 49 , 50 , 51 ]. The current finding on a significant increase of CTR1 in the choroid plexus after D-Pen chelation of Cu is in a good agreement with the literature reports by systematic Cu deficiency induced by restricting dietary Cu [ 24 , 52 ]. Given the anatomical closeness of the choroid plexus to the SVZ in brain ventricle and the fluid communication between the two via the CSF, it is reasonable to postulate that changes in Cu-regulatory functions in the choroid plexus may modulate adult neurogenesis in nearby SVZ.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The choroid plexus plays a critical role in regulating Cu homeostasis in the CSF [ 49 , 50 , 51 ]. The current finding on a significant increase of CTR1 in the choroid plexus after D-Pen chelation of Cu is in a good agreement with the literature reports by systematic Cu deficiency induced by restricting dietary Cu [ 24 , 52 ]. Given the anatomical closeness of the choroid plexus to the SVZ in brain ventricle and the fluid communication between the two via the CSF, it is reasonable to postulate that changes in Cu-regulatory functions in the choroid plexus may modulate adult neurogenesis in nearby SVZ.…”
Section: Discussionsupporting
confidence: 93%
“…Data in this study also showed an upregulated MT3 expression in the SVZ following ICV D-Pen infusion in a dose-dependent manner, which is consistent with the result from the systemic Cu-deficiency model by this lab [ 24 ]. This may indicate a compensatory mechanism by which the Cu-depleted cells demanded more Cu for intracellular storage.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations